A scalable cooperative game theoretic framework for coalitional energy management - Han, L (2020)
The advances in distributed energy resources (DER) propelled power networks worldwide to transition from a unidirectional model to a bidirectional one, under which uncertain and intermittent renewable generation cause load balancing issues. Energy storage as flexible resources have the potential to mitigate the stress on the network, and local energy markets emerged in recent years to encourage efficient management of these resources. However, the formulation of a market scheme that incentivizes such operation by offering profit for all the participants remains an unresolved challenge. This thesis proposes the novel application of cooperative game theory to coalitional energy management, which extends existing cooperative theoretic frameworks to the energy storage operation. The proposed scheme is then proven to have a non-empty core, ensuring the existence of a payoff allocation that incentivizes participation in the grand coalition of all participants.